Pengaruh Kepercayaan Merk, Kualitas Produk, dan Kepuasan Konsumen Terhadap Keputusan Pembelian Produk Sunscreen Wardah Berdasarkan Perspektif Bisnis Islam: Studi pada Pengguna Sunscreen Wardah Mahasiswa Angkatan 2021 UIN Raden Intan Lampung - Khofifah Mahdalena; Zulaikah Zulaikah; Yeni Susanti (Indonesian Economic Review, 2025)
The purchasing decision is the process carried out by individuals, groups, or organizations in selecting and purchasing products or services that they believe will fulfill their needs and desires. This process involves considering various factors, including price, brand trust, product quality, and satisfaction gained from the product or service. The higher the level of consumer trust in the brand, the quality of the product offered, and the level of consumer satisfaction, the greater the impact on the purchasing decision. This study aims to determine the influence of brand trust, product quality, and consumer satisfaction on Wardah sunscreen products from the perspective of Islamic business. The research methodology used is a descriptive quantitative method. The population in this study consists of Wardah sunscreen users from the 2021 batch of UIN Raden Intan Lampung, with a sample size of 98 respondents. The data analysis method used includes validity testing, reliability testing, hypothesis testing, and the coefficient of determination (R²). The results of the study show that: brand trust has a positive and significant effect on the purchasing decision of Wardah sunscreen products with a t-statistic value of 2,524 > 1,98 and a p-value of 0,012 < 0,05. Conversely, product quality does not have a positive and significant effect on the purchasing decision of Wardah sunscreen products, with a t-statistic value of 0,21 < 1,98 and a p-value of 0.817 > 0,05 and consumer satisfaction has a positive and significant effect on the purchasing decision of Wardah sunscreen products, with a t-statistic value of 8,705 > 1,98 and a p-value of 0.000 < 0,05.